PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI PADA ERA DIGITAL DI INDONESIA: STUDI UNDANG - UNDANG PERLINDUNGAN DATA PRIBADI DAN GENERAL DATA PROTECTION REGULATION (GDPR) - Simanjuntak, Predderics Hockop (Esensi Hukum, 2024)
The advancement of digital technology has introduced new challenges in protecting personal data in Indonesia. This article aims to examine the legal protection framework under Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), compare it with the General Data Protection Regulation (GDPR) as an international standard, and assess the effectiveness of its enforcement. The method used is normative juridical with a statute approach. The findings indicate that although the substance of the PDP Law aligns with global standards, its implementation faces significant challenges such as institutional limitations, low public awareness, and the absence of an independent supervisory authority. This article highlights the importance of synergy between regulation, public education, and independent oversight to ensure personal data security in the digital era.